Onset of Celiac Disease after Treatment of Chronic Hepatitis C with Interferon Based Triple Therapy - Amandeep Singh; Nayere Zaeri; Immanuel K. Ho (Case Reports in Hepatology)
Background. Patients treated with interferon (IFN) based therapies may develop exacerbation of autoimmune disease. We herein present the case of a 53-year-old female patient who developed celiac disease (CD) as a result of triple therapy (interferon, ribavirin, and boceprevir) for chronic HCV. Case. 53-year-old Caucasian female with past medical history of IV drug abuse was referred for abnormal LFTs. Laboratory data showed HCV RNA of 4,515,392 IU/mL, HCV genotype 1a, with normal LFTs. She was treated with 4 weeks of pegylated interferon alfa-2a plus ribavirin, followed by triple therapy using boceprevir for a total of 28 weeks. Approximately 4 weeks after initiation of triple therapy patient developed loose nonbloody bowel movements and was also found to have anemia. Biopsies from first and second portions of the duodenum were consistent with CD. The patient was treated with a gluten-free diet. Her intestinal symptoms improved and the hemoglobin returned to normal. Conclusion. Chronic HCV patients being treated with interferon alfa can develop celiac disease during or after therapy. For patients with positive autoantibodies, all-oral-IFN-free regimens should be considered. Celiac disease should be considered in patients who develop CD-like symptoms while on and shortly after cessation of interferon alfa therapy.